Land use, physiography and degradation in the northeastern department Alumine, Neuquén - Mare, Marcos Damián (Centro de Historia Argentina y Americana, 2009)
Kilca River basin is one of the major river systems before the mountain region, located in the center of the province of Neuquen. In this zone, humid climates, the dominant land use is "veranada", which consists of three annual steps of one type of livestock transhumance, based on the exploitation of natural grassland forage. Given the physiographic formation of these landscapes, there is in them a high propensity to develop geomorphological processes of erosion and landslides. Historical factors linked to the evolution of livestock activity in the region on both sides of the mountain axis, have been identified since the late nineteenth century, land use patterns characterized by excessive seasonal stocking. This organization of the activity involved, not just a deterioration of pastures, but also the break out and acceleration of geomorphic processes. The aim of this paper is to analyze the current problems, focusing biophysical processes, linked to social practices. In this sense, we describe and explain physiographic conditions in terms of degree of instability and deterioration of the land